Evaluation of Phytochemicals and Antioxidant Activity of whole plant of Carissa Spinarum - M. N.P. Tejeswari (International Journal of Pharma and Bio Sciences, 2021)
The chronic diseases are rapidly increasing day by day worldwide. Diet and nutrition are important factors in the maintenance of good health conditions throughout life. The physiological and biochemical alterations in the human body may result in the overproduction of free radicals leading to oxidative damage to the biomolecules (e.g. lipids, proteins, DNA). Use of medicinal plant based products has increased recently because of their beneficial effects such as antioxidant, anticancer, hypoglycemic and hypolipidemic activities. The present study was designed to assess the phytochemicals and in vitro antioxidant activity and free radical scavenging activities of Carissa spinarum. The total Phenolic (TPC) and Total Flavonoid Content (TFC) were also assessed. The Total Phenolic content and total Flavonoid content by quantitative method in ethyl acetate and ethanolic extract of Carissa spinarum was found to be 37.233 mg GAE/g, 24.31 mg GAE/g and 35.026mg QRE/g, 21.60 mg QRE/respectively. The TLC based qualitative analysis showed the presence of flavonoids and phenolic compounds. The flavonoids from the ethyl acetate and ethanolic extracts have shown good responses towards antioxidant activity compared with the other remaining extracts. The antioxidant activity of the extracts examined by using different biochemical assays namely diphenylpicrylhydrazyl (DPPH), hydrogen peroxide radical scavenging activity. The assays revealed that the ethyl acetate extract exhibited stronger antioxidant activity than that of ethanolic extract. The IC50 for ethyl acetate and ethanolic extracts were found to be 114.50±0.632 and 119.021±0.623µg/ml respectively in the DPPH method. The IC50 for ethyl acetate and ethanolic extracts were found to be125.400±0.574 and 163.420±0.958µg/ml respectively in the hydrogen Peroxide method. The antioxidant activity of the Carissa spinarum extracts were found to be positively associated with the total phenolic and flavonoid content of the extracts and a positive, significant linear relationship between antioxidant activity and TPC and TFC content showed that phenolic compounds and flavonoids were the dominant antioxidant components in the Carissa spinarum